Membangun Keuangan Syariah Inklusif: Tantangan Dan Peluang Baitul Maal Wat Tamwil Dalam Masyarakat Multikultural - Aslichan, Aslichan; Roro Sri Rejeki Waluyajati; Yeni Huriani; Radea yuli ahmad hambali; Akmal Syawqi Albar; Achnaf Thoriq Al-Khaliel (Institut Muslim Cendekia, 2025)
Baitul Maal wat Tamwil (BMT) is a Sharia-based financial institution that supports financial inclusion and economic empowerment within multicultural societies. The principles of justice, solidarity, and sustainability adopted by BMT enable financial access not only for Muslim communities but also for non-Muslim communities. However, the implementation of BMT faces several challenges, including the stigma of Islamic finance exclusivity, low levels of Sharia financial literacy among the public, and suboptimal regulatory support.This study aims to analyze how the concept of multiculturalism can be integrated into BMT operations to strengthen its role as an inclusive financial model, as well as to identify challenges and strategies for optimizing its implementation. The research method employed is a literature review using a descriptive-critical analysis approach, based on academic sources including journals, books, and recent research reports relevant to multiculturalism, Islamic economics, and BMT practices in plural societies. The findings indicate that BMT has strong potential to serve as an effective inclusive financial model through strategies such as enhancing Sharia financial literacy, strengthening supportive regulations, and integrating financial technology (fintech